Single Ring Isolation With Inferior Line Sparing for Atrial Fibrillation: A Proof-of-Concept Study. (16th April 2021) - Thiyagarajah, Anand; Mahajan, Rajiv; Iwai, Shinsuke; Griffin, Andrew; Mishima, Ricardo S.; Linz, Dominik; Emami, Mehrdad; Kadhim, Kadhim; O'Shea, Catherine J.; Middeldorp, Melissa E.; Lau, Dennis H.; Sanders, Prashanthan
Abstract : Supplemental Digital Content is available in the text.